Mendelian randomization analysis of blood metabolites and immune cell mediators in relation to GVHD and relapse - Xinghao Yu; Yiyin Chen; Lei Lei; Pengfei Li; Dandan Lin; Ying Shen; Chang Hou; Jia Chen; Yi Fan; Yi Jin; Huimin Lu; Depei Wu; et al. (BMC Medicine)
Abstract Background Graft-versus-host disease (GVHD) and relapse are major complications following allogeneic hematopoietic stem cell transplantation (allo-HSCT). Metabolites play crucial roles in immune regulation, but their causal relationships with GVHD and relapse remain unclear. Methods We utilized genetic variants from genome-wide association studies (GWAS) of 309 known metabolites as instrumental variables to evaluate their causal effects on acute GVHD (aGVHD), gut GVHD, chronic GVHD (cGVHD), and relapse in different populations. Multiple causal inference methods, heterogeneity assessments, and pleiotropy tests were conducted to ensure result robustness. Multivariable MR analysis was performed to adjust for potential confounders, and validation MR analysis further confirmed key findings. Mediation MR analysis was employed to explore indirect causal pathways. Results After correction for multiple testing, we identified elevated pyridoxate and proline levels as protective factors against grade 3–4 aGVHD (aGVHD3) and relapse, respectively. Conversely, glycochenodeoxycholate increased the risk of aGVHD3, whereas 1-stearoylglycerophosphoethanolamine had a protective effect. The robustness and stability of these findings were confirmed by multiple causal inference approaches, heterogeneity, and horizontal pleiotropy analyses. Multivariable MR analysis further excluded potential confounding pleiotropic effects. Validation MR analyses supported the causal roles of pyridoxate and 1-stearoylglycerophosphoethanolamine, while mediation MR revealed that pyridoxate influences GVHD directly and indirectly via CD39 + Tregs. Pathway analyses highlighted critical biochemical alterations, including disruptions in bile acid metabolism and the regulatory roles of vitamin B6 derivatives. Finally, clinical metabolic analyses, including direct fecal metabolite measurements, confirmed the protective role of pyridoxate against aGVHD. Conclusions Our findings provide novel insights into the metabolic mechanisms underlying GVHD and relapse after allo-HSCT. Identified metabolites, particularly pyridoxate, may serve as potential therapeutic targets for GVHD prevention and management.